EPIDEMIOLOGY OF HOSPITALIZATIONS FOR COPD IN CURITIBA: TRENDS AND IMPACT OVER A DECADE - Rossini, Julia Delai; Delai Rossini, Katia (Brazilian Journal of Implantology and Health Sciences, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a respiratory condition that significantly affects patients' quality of life and imposes a considerable burden on healthcare systems. Numerous studies highlight variations in COPD hospitalization rates, influenced by factors such as age, climate, and environmental conditions. The primary objective was to analyze COPD hospitalization rates in Curitiba from 2013 to 2023, focusing on age-based variations and significant trends over the years. A retrospective observational study was conducted using data extracted from DATASUS, including all patients hospitalized with a primary diagnosis of COPD, grouped into four age categories: under 40, 40-59, 60-79, and 80 years or older. Descriptive statistics were applied to evaluate annual hospitalizations and identi Between 2013 and 2023, a continuous increase in COPD hospitalizations was observed, with a total rise of 106.3%, from 756 admissions in 2013 to 1,556 in 2023. Hospitalizations varied by age group, with the 60-79 age group being the most representative, accounting for 5,693 admissions (57% of the total). A seasonal variation was also noted, with hospitalization rates peaking during winter months, suggesting an influence of climatic factors such The conclusions of this study emphasize the need for public health strategies targeting COPD prevention and management, especially for more vulnerable age groups, like those aged 60 to 79. Furthermore, the seasonal trends suggest that additional interventions during winter, including vaccination and awareness campaigns, may effectively reduce hospitalizations and mitigate the disease's impact on the population.